Middle school [videorecording (DVD)] : the worst years of my life - Gluck, Griffin; Graham, Lauren, 1967-; Riggle, Rob; Patterson, James, 1947-; Tebbetts, Christopher (CBS Home Entertainment ; Lionsgate, 2017)
Rafe, an imaginative teenager, is tired of his school's obsession with rules at the expense of any and all creativity. Desperate to shake things up, he and his best friends have come up with a plan to break every single rule in the school and let the students run wild.